Investigation of Soil Settlement Due to Different Shape of Load Applied on Soft Soil - Sabrah, Muhamad Aidil Fitri; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2023)
Nowadays, in order to accommodate the rising population, rapid structural development such as buildings have occurred and indirectly resulted in the emergence of numerous structures in less desirable sites. Soft soils like peat and soft clay were prone to failure and collapse. Soil settling has caused several structures to crumble. As a result of soil settlement, several buildings have failed. In addition, people nowadays also designed buildings without considering the properties of the soil that they used as a foundation either it strong enough or not to support the structure. The main objective of this study was to analyze the influence of soil settlement due to different shape of loading applied on soil. This study used two type of soft soil which were peat and soft clay. Laboratory testing was conducted in this study to investigate the index properties of soil such as moisture content, liquid limit and plastic limit. In this study, laboratory physical model was conducted to determine the behavior of soil settlement due to different loading applied on soil and to analyze the influence of soil settlement due to different shape of loading applied on soil. According to laboratory testing that have been done, peat have higher value of moisture content and liquid limit compared to soft clay. The study discovered that peat had a greater soil settlement than soft clay after doing physical model testing. The physical model tests also indicated that the increasing amount of loading applied to the soil increased the amount of soil settlement. Furthermore, the findings of physical model testing revealed that the circular shape of loading causes more soil settlement than the square and rectangular shapes of loading.